Antiplasmodial properties of extracts from Pappea capensis Eckl. & Zeyh. (Sapindaceae) - Bapela, Mahwahwatse Johanna (University of Pretoria, 2022)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2022.